Retrospective study on canine idiopathic epilepsy treatment in primary care practices in the United States - Pompermaier, Elisa; Morrison, Jo Ann; Stabile, Fabio; De Risio, Luisa (Frontiers in Veterinary Science, 2026)
The aim of this study is twofold: to characterize the epidemiology of idiopathic epilepsy (IE) in a large US primary care provider, and to investigate primary care veterinarians’ anti-seizure drugs (ASDs) prescribing practices. A multicenter retrospective study was conducted: Banfield Pet Hospital electronic medical records were searched (01/01/2020–31/12/2023) for dogs aged 6 months to 6 years at first recorded epileptic seizure, with normal general and neurological examinations and unremarkable blood analyses. To further support the IE diagnosis, only dogs prescribed ASDs were included. Signalment, ASDs name and dosing were recorded. Eight-hundred-fifty-three dogs met the inclusion criteria, corresponding to a prevalence of 0.03% (853/2,969,209 over 4 years). Labrador Retriever, Chihuahua and Siberian Husky were the most represented breeds. The median age at diagnosis was 3.3 years. Males accounted for 60.6% of cases. Phenobarbital (34.9%) and levetiracetam (31.3%) were the most prescribed first-line-ASDs, followed by zonisamide (22.9%) and potassium bromide (11.1%). Phenobarbital median maintenance dose was 2.5 mg/kg (IQR 2.2–3.0 mg/kg) per os (PO), with 99.3% of cases receiving it every 12 h. Extended-release levetiracetam was used in 97.4% of cases; the median dose was 29.7 mg/kg (IQR 24.1–34.6 mg/kg) PO, prescribed every 12 h in 87.7% of dogs. Zonisamide was prescribed at a median dose of 5.8 mg/kg (IQR 4.7–7.4 mg/kg) PO every 12 h (98.0%). Potassium bromide maintenance median daily dose was 29.9 mg/kg (IQR 24.0–38.4 mg/kg) PO with a once-daily administration in 83.3% of dogs. Phenobarbital serum concentration was monitored in 77.5% of cases, while bromide serum concentration was monitored in 31.6% of dogs. The estimated prevalence was lower than previous studies, possibly due to strict diagnostic inclusion criteria and data extraction limitations. Labrador Retrievers were the most affected breed, while other predisposed breeds were underrepresented among IE cases. Prescribing practices generally aligned with the ACVIM guidelines, suggesting good implementation of this knowledge in one of the largest US primary care providers. The variability in levetiracetam and potassium bromide dosing highlights the need for updated evidence-based dosing guidelines, while education on the value of therapeutic drug monitoring could support veterinary and pet-owner’s decision making in the management of IE.